(untitled) (Actual Problems of Psychology in Educational Institutions, 2018)
The article is devoted to the problem of successful human life-creation. An attempt is made to detect and analyze the operational-effective component of existential productivity. Emphasizes the role of life-giving actions and life strategies as technologies of life-realization.